A new family of Marx generator based on resonant converter - Zabihi, S.; zare, F.; Ledwich, G.; Ghosh, Arindam; Akiyama, H. (Institute of Electrical and Electronics Engineers ( IEEE ), 2010)
This paper presents a novel topology to generate high voltage with utilization of slow and fast power switches. New concepts used in this topology include numbers of diode-capacitor units in parallel with resonant circuits which are connected to a positive buck-boost converter. The resonant circuit reverses the voltage polarity of the capacitors. This configuration has capability of generating a flexible high voltage with certain number of capacitors. The advantage of this topology is to use slow switches, less number of diodes and capacitors compare to Marx generator. Simulations have been performed to verify the proposed topology.